2022
DOI: 10.3390/ijms232012288
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and Epigenetics of the X and Y Chromosomes in the Sexual Differentiation of the Brain

Abstract: For many decades to date, neuroendocrinologists have delved into the key contribution of gonadal hormones to the generation of sex differences in the developing brain and the expression of sex-specific physiological and behavioral phenotypes in adulthood. However, it was not until recent years that the role of sex chromosomes in the matter started to be seriously explored and unveiled beyond gonadal determination. Now we know that the divergent evolutionary process suffered by X and Y chromosomes has determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 190 publications
0
14
0
Order By: Relevance
“…Furthermore, while most genes have a stable inactivation pattern, a subset of genes exhibit tissue-specific differences in the escape from X inactivation. Thus, differences in the identity and distribution of escape genes between species and tissues may suggest a role for these genes in the evolution of sex differences in specific phenotypes (Berletch et al, 2011).…”
Section: Scc and Organizational Hormonal Effect On The Antidiuretic V...mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, while most genes have a stable inactivation pattern, a subset of genes exhibit tissue-specific differences in the escape from X inactivation. Thus, differences in the identity and distribution of escape genes between species and tissues may suggest a role for these genes in the evolution of sex differences in specific phenotypes (Berletch et al, 2011).…”
Section: Scc and Organizational Hormonal Effect On The Antidiuretic V...mentioning
confidence: 99%
“…The former occur at critical periods of development (on a fetal-neonatal and pubertal time scale), inducing irreversible effects, while activational hormonal influences on sexually dimorphic traits are temporary and may be reversed during fluctuations in the hormonal profile (Arnold and Gorski, 1984;McCarthy et al 2012;Morris et al, 2004). Furthermore, males and females differ not only in their gonads and the consequent hormonal influences, but also carry different sex chromosome complements (SCC, XY for male and XX for females) and thus are influenced through life by different genomes (Cabrera Zapata et al, 2022). For the study of the modulatory effect of SCC on the vasopressorgic sexual dimorphic response, it is important to emphasize that the arginine vasopressin receptor 2 gene, Avpr2, is located in the X-sex chromosome (Berletch et al, 2011) and has been described as having a high probability of escaping X-inactivation (Carrel and Willard, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They directly impact neuronal death pathways and modulate the immune system, with outcomes being dose-dependent and age-related ( McEwen and Milner, 2017 ; Spychala et al, 2017 ; Kim et al, 2019 ). Investigations reveal that females demonstrate post-ischemic upregulation in TNFR1 (tumor necrosis factor receptor-1), IL-17, and natural killer cell signaling pathways, while males manifest increased expression in components of pathways linked to cell development, cellular migration, and pro-inflammatory reactions ( Turtzo et al, 2011 ; Cabrera Zapata et al, 2022 ). Based on these findings, the potential therapeutic role for estrogen in stroke intervention was proposed ( Sohrabji et al, 2019 ).…”
Section: Potential Therapeutic Targetsmentioning
confidence: 99%
“…It has been well documented that the sex chromosome complement is responsible for sexual dimorphism (XX for female and XY for male) ( 18 ). Accordingly, a previous study has assessed sex-related differences in the expression of X chromosome genes in patients with ischemic stroke ( 19 ). The study found that in females, X chromosome-related genes were enriched in TNFR1, interleukin (IL) 17, and natural killer cell signaling pathways, whereas in males, the X chromosome-related genes were highly expressed in pathways involved in cell development, cellular migration, and pro-inflammatory reactions ( 20 , 21 ).…”
Section: Effect Of Sex On Post-stroke Outcomesmentioning
confidence: 99%